1990
DOI: 10.1136/bmj.300.6738.1500
|View full text |Cite
|
Sign up to set email alerts
|

Impaired fibrinolytic capacity and early recurrent spontaneous abortion.

Abstract: The psychological consequences of diets that restrict energy intake are disputed. Our observations suggest that irritability and waking early in the morning were common in the third week of the diet. Whether these behavioural changes were related to decreased plasma concentrations of tryptophan could be investigated by supplementing the diet with tryptophan. There would be considerable interest if supplementation improved the compliance with, and effectiveness of, dieting. Unfortunately, pharmaceutical prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 1 publication
2
16
0
Order By: Relevance
“…As noted by the investigators themselves, those studies were retrospective, the clinical characteristics of the patients were ill-defined, and systematic research for other causes of RM was not performed; thus, selection bias may have been introduced. Only two previous studies have investigated the overall fibrinolytic capacity of RM patients without aPL, and both reports concluded that impaired fibrinolysis could be a risk factor for thrombosis in future untreated pregnancies (21,22). This is in keeping with our study, in which longer CLT in the uRM group was found.…”
Section: Figuresupporting
confidence: 95%
See 3 more Smart Citations
“…As noted by the investigators themselves, those studies were retrospective, the clinical characteristics of the patients were ill-defined, and systematic research for other causes of RM was not performed; thus, selection bias may have been introduced. Only two previous studies have investigated the overall fibrinolytic capacity of RM patients without aPL, and both reports concluded that impaired fibrinolysis could be a risk factor for thrombosis in future untreated pregnancies (21,22). This is in keeping with our study, in which longer CLT in the uRM group was found.…”
Section: Figuresupporting
confidence: 95%
“…Genetic factors may explain between 20% and 62% of the variation in TAFI antigen levels, but the relationships among TAFI polymorphisms, TAFI antigen levels, and the risk of thrombotic complications are not well understood (21,22). We found no differences between groups in the distribution of alleles of the two investigated.…”
Section: Figurementioning
confidence: 44%
See 2 more Smart Citations
“…1 It has been reported that many patients with recurrent miscarriage are in a prothrombotic stage even outside pregnancy, 2 and certain types of thrombophilias have been associated with increased risk for miscarriage. 3 The potential implication of fibrinolytic defects in recurrent miscarrige was first suggested in the early 1990s, 4 but research in this field has only recently become systematic.…”
mentioning
confidence: 99%